The Origins of Democracy in Tribes, City-States and Nation-States - Glassman, Ronald M. (Springer International Publishing : Imprint: Springer, 2017)
This four-part work describes and analyses democracy and despotism in tribes, city-states, and nation states. The theoretical framework used in this work combines Weberian, Aristotelian, evolutionary anthropological, and feminist theories in a comparative-historical context. The dual nature of humans, as both an animal and a consciously aware being, underpins the analysis presented. Part One covers tribes. It uses anthropological literature to describe the "campfire democracy" of the African Bushmen, the Pygmies, and other band societies. Its main focus is on the tribal democracy of the Cheyenne, Iroquois, Huron, and other tribes, and it pays special attention to the role of women in tribal democracies. Part Two describes the city-states of Mesopotamia, Syria, and Canaan-Phoenicia, and includes a section on the theocracy of the Jews. This part focuses on the transition from tribal democracy to city-state democracy in the ancient Middle East - from the Sumerian city-states to the Phoenician. Part Three focuses on the origins of democracy and covers Greece-Mycenaean, Dorian, and the Golden Age. It presents a detailed description of the tribal democracy of Archaic Greece - emphasizing the causal effect of the hoplite-phalanx military formation in egalitarianizing Greek tribal society. Next, it analyses the transition from tribal to city-state democracy-with the new commercial classes engendering the oligarchic and democratic conflicts described by Plato and Aristotle. Part Four describes the Norse tribes as they contacted Rome, the rise of kingships, the renaissance of the city-states, and the parliamentary monarchies of the emerging nation-states. It provides details of the rise of commercial city states in Renaissance Italy, Hanseatic Germany and the Netherlands.
Keywords: Social sciences.; Cultural heritage.; Political science.; Anthropology.; Cultural studies.; elektronické knihy; electronic books